Learning to negotiate - Berkel, Georg, 1971- (New York : Cambridge University Press, 2020)
"Negotiating well is hard. Learning to negotiate is even harder. This new textbook offers sound practical advice for doing both. If you are serious about helping yourself - or others - to become better negotiators, this book is for you. The textbook draws from empirical research in fields as diverse as business, law, neuroscience, game theory, and history. It offers a wealth of examples, case studies, and graphic illustrations. And it blends all this into a coherent framework to guide the practitioner. This is an invaluable book for MBA, law, and other professional students, as well as executives seeking to develop and improve their skills in negotiation"--
Includes bibliographical references and index.
Keywords: Negotiation -- Study and teaching; Mediation -- Study and teaching; Conflict management -- Study and teaching